Two new Oxalis (Oxalidaceae) species, including 5 varieties, from the Richtersveld of South Africa - L. Dreyer, Léanne; Roets, Francois; C. Oberlander, Kenneth (Phytotaxa, 2017)
Two new species of Oxalis (Oxalidaceae) from the Richtersveld are described, namely Oxalis canaliculata and O. magnifolia. These widespread species are morphologically distinct and easily identified, but both contain populations in which individuals consistently differ morphologically from typical varieties. The typical variety of Oxalis canaliculata is widespread throughout the Richtersveld, while O. canaliculata var. trifoliolata is known from a single population and O. canaliculata var. graniticola is known only from granite outcrops. Oxalis magnifolia includes the typical variety that is widespread and Oxalis magnifolia var. reduplicata, which is only known from two populations in close proximity to one another. Morphological characters, preliminary phylogenetic position based on data from the nuclear ITS region, habitat description and formal taxonomic descriptions are provided for all taxa. The diagnostic characters of the new species are compared to all phenotypically similar southern African species.